A call to assess the impacts of electromagnetic fields from subsea cables on the movement ecology of marine migrants. Issue 7 (22nd May 2021) - Klimley, A. Peter; Putman, Nathan F.; Keller, Bryan, A.; Noakes, David
Abstract: The number of subsea cables in the marine environment is likely to grow substantially in the near future. Arrays of energy‐generating windmills or wave power generators are planned for installation in the coastal waters of many countries worldwide. The electricity generated by these and other marine energy sources will be transported to shore through cables with the current and voltage creating electromagnetic fields (EMFs). Furthermore, there are also plans for the installation of undersea cables to interconnect countries and islands for the purpose of sharing power and communications. These also will generate EMFs in the marine environment. While shielding can negate the presence of direct electric fields, induced electric and magnetic fields readily penetrate into the water column. Cables carrying electric current produce anomalies in the earth's main field, which could have the potential for disrupting the migrations of fishes and diverse marine animals that rely on magnetic cues for orientation or navigation. Studies designed to test how these anthropogenic magnetic fields disrupt magnetic orientation have only recently started to be conducted. Given the cultural, economic, and conservation value of many of the species potentially at risk, such work should be immediately prioritized.